Trastornos de personalidad y su incidencia en las relaciones de pareja de los pacientes que asisten al departamento de acogida de salud mental del Hospital Provincial Isidro Ayora. Periodo 2015 - Aguilar Aguinsaca, Andrea Fidelia (2016)
This research investigates the importance of personality disorders in the types of relationships of the patients studied. Therefore aims to identify personality disorders; determine the types of relationships; and the relationship between personaliadad disorders and types of relationships pareja..En research inductive-deductive analytic and synthetic method was used, including techniques and instruments used are: The reviews IPDE Module DSM-IV and the emotional relationships structured questionnaire. The universe was formed department patients HPIA host of a significant sample of 30 patients was considered. According to the results the presence of paranoid disorder, avoidant personality and demonstrated limit; Regarding the types of relationships found, half of them for the impulsive type, while the other half was identified with the elusive type; Likewise the impulsive type of relationship partner is associated more with patients with paranoid personality disorder and avoidant type of relationship partner is associated more with patients with avoidant personality disorders. the head of the host department of Mental Health HPIA is recommended, promote programs of secondary and tertiary intervention to the attention of personality disorders found and finally a psychoeducational proposal to promote mental health and improve relationships is made of patients investigated. KEYWORDS. Personality disorders, of relationships.